Comparative analysis of the equations developed by Jackson et al and ACSM to predict the maximum consumption of oxygenate in students physical therapy (2008)
Objective. Comparativily to analyze the equations developed by Jackson et al, in order to prediction of functional capacity aerobic exercise without making exercise (Nonexercise regression models to estimate peak oxygen consumption [PAR/PAF]) and the calculation made in endless band propose by ACSM (American College of Sports Medicine) in a group of students physical therapy. Patients and methods. They were selected and randomized 36 men and 64 women (N = 100), that they obeyed to the inclusion criteria. The answers from the Nonexercise questionnaire were examined PAR/PAF and their statistical correlation with a protocol of exercise in endless band proposed by the ACSM. Results. When correlating both variables of measurement were similarities in both test of valuation to predict the VO2máx being observed minimum differences of agreement (14 individuals). Of the total of evaluated, 86 individuals agree in the two tests, with p and lt; 0,05. The index of agreement of the study was of r = 0,78. Conclusions. Both criteria of valuation, they demonstrate results over the predicted values very overestimating the aerobic capacity in this population, whose prevalence of inactivity physical is marked. It is possible to write down, that the Nonexercise regression models to estimate peak oxygen consumption (PAR/PAF) like subjective procedure, it can arrive to be used like soft technology in studies epidemiologists when it is not counted on the necessary infrastructure.